Readability analysis of Malaysian short stories in English - Imran Ho Abdullah,; Ruzy Suliza Hashim, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2007)
The main objective of this paper is to examine the readability statistics of a corpus of Malaysian short stories in English with reference to a corpus of established canonical short stories written by native speakers. The short stories selected for analysis comprise twelve short stories published in the New Straits Times. The reference corpus consists of seven short stories that have been at some stage been recommended as texts for the English Literature syllabus in the Kurikulum Baru Sekolah Menengah (KBSM) / Secondary Schools New Curriculum. Three readability statistics are generated (Flesch Reading ease, Flesch grade level and Gunning Fog index) for the stories. The readability scores of these stories are then compared to the readability of the recommended texts on similar themes in order to assess their suitability for Malaysian ESL adolescent readers. The analysis reveal that both the Malaysian corpus and the recommended text falls within the range of US grade 6.0 – 8.5 with the Malaysian corpus having the added advantage in terms of cultural and local references